THE ATHEISTIC ARGUMENT FROM OUTRAGEOUSNESS. Issue 48 (7th February 2018) - Frances, Bryan
Abstract : When pressed, many atheists offer three reasons why they reject theism: there is strong evidence against theism, there is no strong evidence for theism, and theism is so outrageous that it needs a great deal of support in order for us to believe it in a reasonable manner. I examine the third reason, arguing that it fails.